أصول التقاضي في الوثيقة العمرية - عمر محمد علي إدريس, محمود (جامعة الوادي - University of Eloued, 2020)
ملخص البحث: اشتملت هذه الدراسة على إبراز أصول التقاضي في الوثيقة العمرية، من خلال ثلاثة مباحث، مبحث تمهيدي في بيان مفهوم أصول التقاضي وأهميتها وسياسة عمر القضائية، ومبحث ثان في نص الوثيقة العمرية وموقف الفقهاء الذين أجمعوا على قبولها واعتماد العمل بما فيها، وبيان شبهة من شكك في نستبها وطعن في صحتها، ثم المبحث الثالث في استخلاص أصول التقاضي التي اشتملت عليها الوثيقة العمرية، من ضرورة القضاء بين الناس، وإقامة العدل بينهم، وما يجب أن تكون عليه مصادر الأحكام القضائية من الاعتماد على الكتاب والسنة والإجماع والقياس ثم الاجتهاد فيما لا نص من الأحكام، وفهم القضية واستيعابها قبل إصدار الحكم فيها، واعتدال حال القاضي أثناء القضاء، وتمكين الخصم من الإدلاء بحجته، وأن تكون مهمة القاضي الأولى التسوية بين الخصوم تحقيقاً لمبدأ العدل والمساواة، ومحاولة الاصلاح بينهم قبل إصدار الحكم، ثم إنفاذ الحكم والإلزام به متى تحققت الشروط والأسباب وانتفت الموانع، ورجوع القاضي عما حكم إن بان له وجه الخطأ، أو تغيّر اجتهاده، فلا يكون الاجتهاد الأول مانعًا من العمل بالثاني إذا ظهر أنه الحق، فالرجوع إلى الحق خير من التمادي في الباطل، مع تحري الإخلاص في الحكم بين الناس. وتمت دراسة هذه الأصول دراسية فقهية مقارنة للمسائل الخلافية بالرجوع إلى المصادر المعتبرة في كل مذهب، مع الإفادة من المؤلفات المعاصرة فيما له صلة بالموضوع وختمت الدراسة بأهم النتائج والتوصيات. - الكلمات المفتاحية: أصول. التقاضي. الحكم. العدل. Research Summary: This study included highlighting the principles of litigation in the Covenant of Omar, through three topics, a preliminary discussion in the indication of the concept of Fundamentals of litigation and their importance and Omar's Judicial policy, and a second topic in the text of the covenant of Omar and the viewpoint of scholars who unanimously agreed to act according to it, and to clarify the suspicion of questioning its attribution or challenging its validity. The third topic is in the extraction of the principles of litigation contained in the Covenant of Omar, the importance of judicature application among people and the administration of justice among them, and what must be the sources of judicial rulings of relying on the book , Sunna , consensus, measurement, and finally ijtihad in the absence of provisions, understand and comprehension of the case before sentencing and the sobriety of the judge during the judiciary to enable the opponent to make his argument, and that the judge's first task is to reconcile the adversaries towards achieving the principle of justice and equality, always endeavors to resolve disputes between adversaries before ruling, and then enforce the judgment and make it mandatory when the conditions and reasons are met and restrictions are absent and may change his judgment when he perceives inaccuracy, or change his ijtihad, and ijtihad should not prevent from applying of the other opinion if it is proved to be genuine and authentic, because resorting to the truth is better than remaining in continuous falsehood while achieving honesty in governance among people. The study of the fundamentals of this jurisprudence in comparison with the controversial issues by reference to the sources considered in each doctrine has been achieved by taking advantage of the contemporary literature associated with it, the study concluded with the most important findings and recommendations
دراسة فقهية مقارنة
مقال في مجلة الشهاب بجامعة الوادي
Keywords: أصول ; التقاضي ; الحكم ; العدل ; الوثيقة. ; الأحكام